Analysis of the Level of Public Transportation Accessibility at the Type A Bimoku Inter-Border Terminal (Albn), Kupang City - Kresnawati, Ajeng D; Sinaga, Elly Adriani; Sarjana, Sri (International Journal Labs, 2024)
The Bimoku Type A Cross Border Terminal located in Kupang City, East Nusa Tenggara, is a cross-border transport hub that has been operating since 2023. However, its performance has not been optimal and accessibility to this terminal is still low. This study aims to analyse the level of accessibility of public transport to the Type A Bimoku Cross-Border Terminal in Kupang City and provide recommendations for improving performance. The method used is Generalised Cost (GC) analysis with a do nothing and do something approach. The results show that the largest GC values in the existing conditions are in the Fatukoa, Naioni, and Bello zones. The implementation of the new route network in the do something scenario succeeded in significantly reducing the GC value, thereby increasing the accessibility and efficiency of transportation to the Bimoku Type A Cross Border Terminal in Kupang City. Recommendations are to develop new public transport routes and improve intermodal connectivity to support overall terminal performance.